ORAL CANDIDIASIS IN HIV PATIENT SUFFERING PNEUMOCYSTIC CARINII PNEUMONIA - Dahlia Riyanto; Rindang Tanjungsari; Tri Pudy Asmarawati; Desiana Radithia (Dentino : Jurnal Kedokteran Gigi, 2020)
Background: HIV/AIDS infection provoked opportunistic infection systhemically and intraorally. Pneumocystic carinii pneumonia (PCP) and Oral candidiasis (OC) is the most prevalent opportunistic infection among HIV/AIDS patient and may serve as indicator of low CD4 count in HIV infection. Objective: This paper reports management of oral candidiasis in pneumocystic carinii pneumonia that affects a patient with HIV. Case: A 39 year-old man was hospitalized for pneumocystic carinii pneumonia with weakness of gait and emaciated posture. He was also diagnosed of HIV/AIDS infection through CD4 count and HIV rapid test. Intraoral white patches was reported occured within 2 days being hospitalized. Several tests were ordered resulting, metabolic acidosis, CD4 count were 10 cells/μL, HIV rapid test (ICT) was reactive for 3 methods, and microbiologic examination was positif to C.albicans from the smear of white plaque. The patient also diagnosed with OC pseudomembranous type. Case Management: Patient was treated using intravenous fluconazole 100 mg/day for five days and antiseptic mouthwash. Recovery was achieved within 3 weeks follow-up along with given anti retroviral (ARV) treatment by the internist. Conclusion: Management of OC in HIV/AIDS patient with PCP infection in this case were used systemic antifungal and antiseptic mouthwash. The multidiciplinary approach in managing this case obtained successful therapy.